MENGEMBANGKAN MOTORIK HALUS ANAK MELALUI PROYEK KREASI KARYA DAUR ULANG PADA KELOMPOK B TK HIDAYAH - Juliana, Tiurma; Novitawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine teacher activities and children’s activities, and to analyze improvements in children’s fine motor skills in cutting and pasting. The research approach used was a qualitative approach in the form of Classroom Action Research (CAR), conducted over four sessions. The study was conducted in Group B of Hidayah Kindergarten in East Banjarmasin, consisting of 14 children. Data collection methods included observation, documentation, and assessment of fine motor skills development. Data analysis techniques using qualitative descriptive analysis are illustrated with tables and graphs. The results of the study indicate that cutting and pasting activities as part of a creative recycling project can enhance teacher engagement, children’s engagement, and children’s fine motor skills development. Teacher engagement increased from a score of 15 (rated “Fairly Good”) to a score of 26 (rated “Very Good”). Children’s activity levels increased from 29% under the “All Children Inactive” criterion to 86% under the “All Children Active” criterion. Children’s fine motor development scores improved from 29% to 86% under the “Developing Very Well” criterion. The results of this study successfully increased teacher activity, child activity, and children’s fine motor development outcomes.